KETERCAPAIAN KURIKULUM TINGKAT SATUAN PENDIDIKAN SEKOLAH MENENGAH KEJURUAN DI KOTA YOGYAKARTA - Yunanto, Dwi (Vidya Karya Jurnal Kependidikan, 2013)
The research has the objective to evaluate the implimentation of KTSP at vocational school in Yogyakarta. The research result says that (1) the implimentation achievement of variable descriptive test result relating content context and the implimentation of education policy with the score 64.51% is categorized sufficient, (2) the support of school to the implimentation of KTSP with the score 75.69% is categorized good, (3) the implimentation of readiness of school program and school resources with the score 80.58% is categorized good, (4) the implimentation of process involving teachers and students is categorized good, (5) and the problem in implimenting KTSP is fund, facilities, and the lack of knowledge about KTSP for vocational school.